Biochemical analysis of Orai1 mutants derived from a cancer database - Attar, Bahareh (Jihočeská univerzita, 2023)
This thesis examines Orai 1 mutants in cancer using chemichulation detection. It studies human-specific mutations and compares them to Drosophila melanogaster mutations. Pymol is used to visualize structural variations. The research aims to understand the molecular mechanisms of Orai 1 in cancer, potentially guiding the development of targeted cancer therapies.The objective of this study involves employing PyMOL, along with pertinent references, to explore the chemiluminescence detection mechanism of membranes featuring the H134A+R91C mutation and the R91C mutation in humans. This investigation extends to a comparative analysis with the closed-channel 4HKS(K163W) mutation observed in Drosophila melanogaster, which shares similarities with the R91W mutation in humans. Additionally, the study encompasses the open- channel 6BBF (H206A) mutation in Drosophila melanogaster, akin to the H134A+R91C mutation in humans. Through these analyses, a deeper understanding of the chemiluminescence properties of these mutations across species can be gained.
Biochemical analysis of Orai1 mutants derived from a cancer database
Biochemical analysis of Orai1 mutants derived from a cancer database
Keywords: open-channel 6BBF (H206A) similar to H134A+R91C mutation in humans; closed-channel 4HKS(K163W) mutation similar to R91W mutation in humans; open-channel 6BBF (H206A) similar to H134A+R91C mutation in humans; closed-channel 4HKS(K163W) mutation similar to R91W mutation in humans